KONSTRUKSI MAKNA SELENDANG SEBAGAI SENJATA DALAM FILM PAHLAWAN SUPER WANITA ‘SRI ASIH’ (2022) - Devi Nirmala Muthia Sayekti (Akademi Seni dan Desain Indonesia Surakarta, 2023)
This paper is aimed to observe the presence of scarf employed by woman superhero in the movie entitled ‘Sri Asih’ (2022). Up to this day, the function of scarf as a part of costume, either for dancing or other performances, is commonly used for property. It was a few numbers of studies observing the meaning attached to scarf when it is worn by the performer, or in other context. Meanwhile, the story of Sri Asih in its movie can construct new meaning related to the presence of the scarf. This research is using qualitative and descriptive way. By employing the theory of Reading Images by Theo van Leeuwen and Gunther Kress, this paper tries to explore how the presence of scarf can construct a new meaning beyond such a property of costume. Even more, the way of making meaning of its power to the Sri Asih’s scarf also prove that representation of scarf for women is closely related in Nusantara’s culture context. A number of women’s role often need scarf as their ‘weapon’ to walk on their job.Keywords: Sri Asih Movie, Analysis of Shawl, Costume, Semiotics, Reading Images